Internalization of Religious Moderation in Islamic Religious Education Learning - Khoir, Fatakhul; Rahmat; Zamroni, M Afif (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
Education must strive to cultivate a broad and positive perspective. Moderation represents a balanced attitude, avoiding extreme biases. Islamic Education (PAI) learning can foster this moderation by instilling values of tolerance, anti-radicalism, and nationalism, essential for maintaining national unity. This study, conducted at SMPN 1 Prambanan Klaten, employs a qualitative approach with a case study methodology to address societal issues. The research observes the internalization of religious moderation through PAI to shape students' attitudes. The study aims to analyze the process of internalizing religious moderation in PAI at SMPN 1 Prambanan Klaten. Internalizing religious moderation is crucial for developing students who respect the diverse religions, ethnicities, and cultures in Indonesia. This process includes four core values: national commitment, tolerance, respect for local culture, and an anti-radicalism stance. Data were collected through interviews, observations, and documentation involving the principal, PAI teachers, and students. The findings indicate successful internalization of religious moderation within PAI learning. Students exhibit tolerance, respect for diversity, and national commitment. Furthermore, this internalization has led to improved student discipline, appreciation for diversity, and rejection of radicalism and violence. It also enhances nationalism and awareness of preserving local culture. Consequently, PAI learning at SMPN 1 Prambanan Klaten has effectively created a harmonious environment and supported the development of inclusive student character.